Pengaruh Program Pelatihan dan Pengembangan Karyawan terhadap Kinerja Karyawan (Studi Kasus pada PT. Astra Internasional Tbk. AUTO 2000 Cabang Malang Sutoyo) - Erna Resmiatini; Saifuddin, Muhammad (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2023)
In this research, the author intends to test the influence of employee training and development programs on the employee performance of PT Astra Internasional Tbk., AUTO2000 Malang Sutoyo. Data was collected using a questionnaire, distributed to 50 service employees. Testing was carried out using quantitative methods, especially multiple regression analysis. The research results show that partially the training program has no influence on employee performance. This is different from development programs which are proven to influence employee performance positively and significantly. However, simultaneously, the employee training and development program that has been carried out by PT. Astra Internasional Tbk., AUTO2000 Malang Sutoyo in the service section has been proven to influence employee performance. Keywords: Training, Development, Employee Performance.